Pre‐Sealing of Endodontic Access Cavities for the Preservation of Anterior Teeth Fracture Resistance - Fereshteh Shafiei; Maryam S. Tavangar (Wiley, 2024)
ABSTRACT Objective Sodium hypochlorite solution (NaOCl) is an effective canal irrigant but interferes with the mechanical features of dentin and the bonding capability of adhesives when restoring endodontically treated teeth. This study evaluated whether access cavity resin sealing before using canal irrigant would augment the resistance of endodontically treated anterior teeth against fracture. Methods Sixty maxillary incisors underwent endodontic treatment in five groups (n = 12). Irrigation with 5.25% NaOCl and 17% ethylenediaminetetraacetic acid (EDTA) was performed in all groups except for Group 5. After root canal obturation, in Group 1, the access cavity was kept unrestored. In Group 2, immediate restoration after obturation was achieved. For Group 3, delayed restoration after 1 week was provided. In Group 4 (pre‐sealed), before canal irrigation, the dentin surface of access cavities was sealed using self‐adhesive composite resin (Vertise Flow) and then restored after obturation. In Group 5, which was saline irrigated, immediate restoration was performed. After storage and thermal cycling for 5000 cycles at 5°C-55°C with a dwell time of 15 s and a transfer time of 5 s, teeth were statically loaded by a universal testing machine until a fracture occurred. Data were collected as the fracture resistance (FR) and analyzed using the one‐way analysis of variance and Tukey's tests. Results FR significantly differed between all groups (p < 0.001). The lowest FR was recorded in the unrestored group (284 ± 86 N), which was not statistically different from the immediately restored group (p = 0.065). The pre‐sealed group exhibited the highest FR value (810 ± 127 N, p ≤ 0.02 vs. other groups). The FR of the saline‐irrigated and delayed restored groups was almost similar (p = 0.13). Conclusions NaOCl/EDTA irrigation resulted in an adverse effect on FR. Delayed restoration could reduce this adverse effect. Access cavity pre‐sealing with flowable composites led to a higher FR than conventional methods and may be considered an effective step during treatment procedures.